2014
DOI: 10.1038/cddis.2014.334
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of 2-(piperidinoethoxyphenyl)-3-(4-hydroxyphenyl)-2H-benzo(b)pyran (K-1) on human primary endometrial hyperplasial cells mediated via combined suppression of Wnt/β-catenin signaling and PI3K/Akt survival pathway

Abstract: Endometrial hyperplasia is a precursor to the most common gynecologic cancer diagnosed in women. Apart from estrogenic induction, aberrant activation of the Wnt/β-catenin signal is well known to correlate with endometrial hyperplasia and its carcinoma. The benzopyran compound 2-(piperidinoethoxyphenyl)-3-(4-hydroxyphenyl)-2H-benzo (b) pyran(K-1), a potent antiestrogenic agent, has been shown to have apoptosis-inducing activity in rat uterine hyperplasia. The current study was undertaken to explore the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…We also observed that PNU led to increased mRNA expression of the beta-catenin target genes CCND1 and AXIN2 . In agreement, it has been shown that the Wnt/beta-catenin pathway inhibition resulted in increased AXIN2 mRNA expression in endometrial cells [ 31 ]. Furthermore, our data suggest a potential effect on beta-catenin-dependent transcription, a mechanism of action that has been reported for other inhibitors of the Tcf/beta-catenin complex [ 18 , 32 ].…”
Section: Discussionsupporting
confidence: 62%
“…We also observed that PNU led to increased mRNA expression of the beta-catenin target genes CCND1 and AXIN2 . In agreement, it has been shown that the Wnt/beta-catenin pathway inhibition resulted in increased AXIN2 mRNA expression in endometrial cells [ 31 ]. Furthermore, our data suggest a potential effect on beta-catenin-dependent transcription, a mechanism of action that has been reported for other inhibitors of the Tcf/beta-catenin complex [ 18 , 32 ].…”
Section: Discussionsupporting
confidence: 62%
“…In general, it is thought that endometrial cancer develops from atypical endometrial hyperplasia, a precursor lesion of endometrial cancer [32]. Genetic abnormalities or mutations such as p53 mutations, KRAS mutations, phosphatidylinositol 3-kinase (PI3 K) mutations, abnormal PTEN expression, and accumulation of β catenin are known to be involved in malignant transformation of normal endometrium [33,34]. In [ ( F i g .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of this compound to inhibit uterine growth is attributed to its ability to antagonize estrogen action and apoptosis-inducing activities [ 162 ]. The activity of this compound has also been validated in primary cell culture of human atypical EH cells suggesting its potential use as a new targeted therapy for EH via inhibition of Wnt signaling, as well as inhibition of cell survival pathway [ 163 ].…”
Section: Limitations Of Existing Therapies Need For Further Researchmentioning
confidence: 99%